2012
DOI: 10.4236/jmp.2012.311222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Doping on the Properties of ZnO Thin Films Prepared by Spray Pyrolysis

Abstract: Layers of transparent and conductive Sn-doped zinc oxide (ZnO) have been prepared using chemical reactive liquid phase (spray) method on glass substrates. X-ray diffraction analysis shows that the obtained layers show preferential grains orientation along the direction (002). Microstructural analysis indicates that the thickness of the deposited films is independent of Sn content, i.e. 408 nm, and that the average grain size increases with increasing Sn content, ranging from 31 nm to 42 nm. The value of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…It is also assumed that the absorption coefficient near the band edge shows an exponential dependence on photon energy and this dependence is given as follows [28] [29] ( )…”
Section: 3uv-visible Spectrophotometer (U-vis)mentioning
confidence: 99%
“…It is also assumed that the absorption coefficient near the band edge shows an exponential dependence on photon energy and this dependence is given as follows [28] [29] ( )…”
Section: 3uv-visible Spectrophotometer (U-vis)mentioning
confidence: 99%
“…AJILI, et al (2013) [17] suggests that the transmittance of the ZnO layer decreases for higher tin percentage, due to the formation of a thicker layer that reduces the transmittance of the film. CHAHMAT, et al (2012) [21] observed lower transmittance range when increasing the tin doping from 4% to 6% and 8%. GANESH, et al (2017) [22] also observed a tendency for lower transmittance at higher tin load and indicates the thickness as the main reason for such an event.…”
Section: Optical Characterizationmentioning
confidence: 95%
“…В соответствии с [29,30] величина E g со-ответствовала точке пересечения с осью энергий hν прямой, полученной экстраполяцией на hν линейной части зависимости функции Кубелки−Мунка. Степень разупорядочения структуры CuI оценивали по величине энергии Урбаха E o , которую определяли, согласно [31], как котангенс угла наклона линейного участка зависимости ln[− ln(T o )] от hν вблизи значения hν = E g ∼ 3 эВ. Фактор светорассеяния (H f , Haze factor) рассчитывали в соответствии с [27] как отношение диффузного отражения R к полному отражению (сумме диффузного и зеркального отражений).…”
Section: методика экспериментаunclassified